Anti-malarial activity and toxicity of Aspidosperma nitidum Benth: a plant used in traditional medicine in the Brazilian Amazon (Research, Society and Development, 2020)
The objective of this work was to evaluate the antiplasmodial activity and toxicity of the extract and fractions obtained from the bark of Aspidosperma nitidum. The ethanol extract obtained from the powdered bark of plants was acid-base partitioned and phytochemically analyzed. The antiplasmodial activity, in vivo antimalarial activity and in vitro cytotoxicity were acessed. The selectivity index (SI) was calculated. The acute oral toxicity and pathological effects, of the ethanol extract was evaluated in mice. The major constituent of the ethanol extract was suggestive of a β-carboline chromophore. The alkaloid and neutral fractions contained compounds with an aspidospermine core as the major constituent. The ethanol extract (IC50 = 3.60 µg/mL), neutral fraction (IC50 = 3.34 µg/mL) and alkaloid fraction (IC50= 2.32 µg/mL) showed high activity against P. falciparum (W2 strain). The ethanol extract and the alkaloid fraction reduced 80% of the parasitemia of P. berghei (ANKA)-infected mice (dose of 500 mg/kg) in the 5th day, which was not sustainable at the 8th day. A similar result was obtained for chloroquine. The ethanol extract (CC50 = 410.65 µg/mL; SI = 114.07), neutral fraction (CC50 = 452.53 µg/mL; SI = 135.49), and alkaloid fraction (CC50 =346.73 µg/mL; SI 149.45) demonstrated low cytotoxicity and high SI. The ethanol extract (5000 mg/kg; gavage) presented low acute oral toxicity, with no clinical or anatomopathological modifications being observed (in comparison to the control group). In vitro studies with a chloroquine-resistant clone of P. falciparum confirmed the antiplasmodial activity of the A. nitidum ethanol extract, and its fractions had low cytotoxicity for HepG2 cells. In vivo studies with P. berghei–infected mice and acute toxicity studies corroborated these results.